Metformina como fator protetor independente para doença arterial coronariana - Dinízio, Deivison Souto (2018)
Background: Coronary Artery Disease (CAD) has Diabetes Mellitus (DM) as one of its risk factors. Metformin has been studied for its effects on cardiovascular risk factors and also directly in the heart, with studies on its action on atherosclerosis. Objective: To evaluate the use of metformin as a protection factor for CAD. Methods: Observational, cross-sectional and analytical study with 11551 patients with suspected and / or established CAD undergoing PSE (physical stress echocardiography). Patients were divided into two groups according to the presence or absence of DM. Patients who had previously established evidence of CAD were classified as having chronic CAD. Results: The group of diabetics had higher age (60.9 ± 9.3 years vs 56.8 ± 11.5, p <0.0001). The frequency of chronic CAD, DM and use of metformin in the study was 13.9%, 12.5% and 4.8%, respectively. Regarding the evaluation of the occurrence of CAD and luminal reduction in coronary cineangiography, there was a reduction in the occurrence of CAD and injury in diabetic and non-diabetic patients when they were using metformin. Conclusion: In patients with chronic CAD or with luminal reduction in coronary cineangiography, the use of metformin reduced the occurrence of this condition among diabetic patients or not, suggesting metformin acts as a protective factor for the occurrence of chronic CAD and luminal reduction.